Rozwiązane

Usuń niewymierność:
[tex]\frac{\sqrt{6} }{2\sqrt{3}+\sqrt{2}}[/tex]
[tex]\frac{1}{\sqrt[3]{3}-\sqrt[3]{2}}[/tex]

Dzięki :3



Odpowiedź :

Odpowiedź:

[tex]\frac{\sqrt{6}}{(2\sqrt{3}+\sqrt{2}) } * (\frac{2\sqrt{3} - \sqrt{2}) }{(2\sqrt{3}- \sqrt{2})} = \frac{2\sqrt{18}-\sqrt{12} }{12-2} = \frac{6\sqrt{2}-2\sqrt{3 } }{10} = \frac{3\sqrt{2}-\sqrt{3} }{5}[/tex]

Do tego drugiego trzeba zastosować wzór skróconego mnożenia [tex]a^3-b^3[/tex]

[tex]\frac{1}{\sqrt[3]{3}-\sqrt[3]{2} } *\frac{\sqrt[3]{9}+\sqrt[3]{6}+\sqrt[3]{4} }{\sqrt[3]{9}+\sqrt[3]{6}+\sqrt[3]{4}} = \frac{\sqrt[3]{9}+\sqrt[3]{6}+\sqrt[3]{4}}{3-2} =\frac{\sqrt[3]{9}+\sqrt[3]{6}+\sqrt[3]{4}}{1}= \sqrt[3]{9}+\sqrt[3]{6}+\sqrt[3]{4}[/tex]

Szczegółowe wyjaśnienie: